Gender in Uduk - Killian, Don (My University, 2019)
Uduk, a Koman language spoken on the border of Ethiopia and Sudan, evinces a number of unusual characteristics in its system of gender marking. Uduk has two gender classes, with agreement displayed primarily in the verbal system and adjacent case-marking particles. In contrast to related Koman languages, howeversemantics play a minimal role in class assignment, unrelated to biological sex. Furthermore, as biological sex does not play a role in gender assignment in general, personal pronouns do not differentiate gender in any person. Instead, all personal pronouns are assigned to Class 1 in the same manner that nouns would be. Lastly, Uduk shows some unorthodox aspects in the way it indexes gender on verbs, using what might be considered subtractive morphology. This article looks at the complexity and features of gender in Uduk from a typological perspective; despite some unorthodox and atypical typological features, however, the system does not appear to be complex.
Keywords: Uduk; gender; Koman